Backboard, backlight module and display - KANG BAOHONG; JIANG XINGJIA (2023)
The invention discloses a back plate, a backlight module and a display. Wherein the back plate comprises a bottom plate and a side plate connected with the bottom plate, the bottom plate and the side plate jointly define a containing cavity, the side plate comprises a light guide part, and the light guide part is used for guiding part of light in the containing cavity out of the containing cavity. According to the technical scheme, the side plate of the back plate comprises the light guide part, and the light guide part can guide part of light in the containing cavity of the back plate out of the containing cavity, so that the reflection amount of the light close to the side plate in the containing cavity can be reduced, the intensity of the light is further weakened, and the situation that light leaks from the edge of the backlight module applying the back plate is relieved or eliminated. And when the side plate comprises the light guide part, the effect of weakening the intensity of the light at the edge ca